Orbital and Eye Lid Tuberculosis - Khalid, Abdul; Bukhari, Murtaza; Baaiq, Tariq (International Journal of Pathology, 2018)
Tuberculosis of eye lid and orbit is uncommon even in endemic countries of Asia. We report a case of25 year old patient presented with a sinus above the left orbital crease and growth on bulbar aspect ofupper eye lid. She also had a cold paraspinal abscess. It was associated with systemic symptoms ofweight loss, evening pyrexia and weight loss. Her evaluation and FNAC confirmed the diagnosis andshe received anti tuberculous treatment with improvement in six weeks. The co- existence of orbitaland lid tuberculosis has not been reported before